Hak Pilih Perempuan Dalam Sistem Demokrasi dan Hukum Tata Negara Islam - Bukhari, Bukhari; Anwar, Anwar; Anwar (Prodi Hukum Tata Negara Islam (Siyasah Syar'iyyah) STAIN Teungku Dirundeng Meulaboh, 2025)
Women's voting rights are part of human rights guaranteed by modern democratic systems and the Indonesian Constitution. However, women's political participation is often hindered by social, cultural, and conservative religious interpretations. This article aims to analyze women's suffrage from two perspectives: the constitutional democratic system and Islamic constitutional law. The study employs a normative-juridical approach through literature review of both positive legal documents and classical as well as contemporary Islamic texts. The findings show that the Indonesian Constitution—particularly the 1945 Constitution and the Election Law—ensures equal political rights without gender discrimination. From the Islamic perspective, although some classical scholars rejected women's political roles based on certain hadiths, many contemporary scholars permit their participation based on maqasid al-shari'ah, such as justice and public interest (maslahah). Islamic history also records women's involvement in significant events like the Pledges of Aqabah and Ridwan. This article recommends a contextual reinterpretation of religious texts so they do not become barriers to women's political engagement. Thus, women's suffrage can be legitimately accepted in both the constitutional democratic system and a progressive, inclusive interpretation of Islamic constitutional law.